1986
DOI: 10.1017/s0003356100017803
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutrition on the reproductive performance of first-litter sows 3. The response to graded increases in food intake during lactation

Abstract: Seventy-two animals were used in an experiment to study the response of first-litter sows to graded increases in daily food intake during a 28-day lactation. Six food intakes, ranging from 1-5 to 4-8 kg/day were compared. The results showed that both live-weight loss and backfat loss during lactation increased linearly as food intake decreased (P < 0-01).Subsequent ovulation rate was unaffected by food intake but both weaning to mating interval (Y,, days) and the proportion of sows exhibiting oestrus within 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
2
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 7 publications
1
23
2
1
Order By: Relevance
“…An inadequate nutrient and energy intake is expected to result in extended wean-to-oestrus interval with a lower percentage of sows in oestrus within seven days of weaning, reduced pregnancy rate and reduced embryo survival (Quesnel et al 1998;Aherne et al 1999). Especially protein restriction during lactation can have a negative impact on post weaning ovulation rate (Mejia-Guadarrama et al 2002), whereas a crucial body protein mass loss can rapidly reduce ovarian function (Clowes et al 2003) and increase the time required for expression of oestrus after weaning (King and Dunkin 1986;Koketsu et al 1996). In contrast to the above, we found that overgrown toes in front and rear feet were associated with more live-born and weaned piglets as well as with a shorter wean-to-first service interval.…”
Section: Discussioncontrasting
confidence: 77%
“…An inadequate nutrient and energy intake is expected to result in extended wean-to-oestrus interval with a lower percentage of sows in oestrus within seven days of weaning, reduced pregnancy rate and reduced embryo survival (Quesnel et al 1998;Aherne et al 1999). Especially protein restriction during lactation can have a negative impact on post weaning ovulation rate (Mejia-Guadarrama et al 2002), whereas a crucial body protein mass loss can rapidly reduce ovarian function (Clowes et al 2003) and increase the time required for expression of oestrus after weaning (King and Dunkin 1986;Koketsu et al 1996). In contrast to the above, we found that overgrown toes in front and rear feet were associated with more live-born and weaned piglets as well as with a shorter wean-to-first service interval.…”
Section: Discussioncontrasting
confidence: 77%
“…In this study, an increase in feed intake did not reduce the weaningto-estrous interval. King and Dunkin (1986) reported a positive linear effect of ME feed intake on the weaning-to-estrous interval. Vesseur et al (1994b) reviewed the possible direct effects of the weaning-to-estrous interval on reproductive performance, and concluded that a short weaningto-estrous interval tended to result in more large litters.…”
Section: Discussionmentioning
confidence: 97%
“…In support, King and Williams (1984) compared the reproductive performance of first-litter sows on ad libitum (4-5 kg/day) and 2-0 kg/day feeding levels over a 32-day lactation and reported that piglets of the sows fed ad libitum grew relatively (but not statistically significantly) faster to weaning. King and Dunkin (1986), who compared six graded feeding levels (1-5 to 5-0 kg/day) for firstlitter sows over a 28-day lactation, found a reduction in piglet weaning weights on the three lowest levels of feeding resulting from a lower growth rate during the last 7 days of lactation. In a similar lactation period Reese, Moser, Peo, Lewis, Zimmerman, Kinder and Stroup (1982) reported a reduction in the weaning weights of piglets sucking first-litter sows which had low food intakes in lactation.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies on lactation feeding level and rebreeding efficiency (albeit with firstlitter sows) favour a high food intake in lactation. King and Williams (1984), in comparing lactation feeding levels of 2-0 and 4-5 kg/day, found that sows on the lower level of feeding took longer to return to oestrus after weaning while King and Dunkin (1986), who used six graded feeding levels in lactation, reported a delayed weaning to conception interval on the two lowest feeding levels (1-5 and 2-2 kg/day) but not on the others (2-9 to 5-0 kg/day). Reese et al (1982) also found that restriction of energy intake in lactation delayed the onset of oestrus post weaning.…”
Section: Discussionmentioning
confidence: 99%